2022
DOI: 10.1038/s41416-022-01933-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of tumour-infiltrating immune cells in biliary carcinogenesis

Abstract: Background Intraductal papillary neoplasms (IPN) and biliary epithelial neoplasia (BilIN) are well‐defined precursor lesions of biliary tract carcinoma (BTC). The aim of this study was to provide a comprehensive characterisation of the inflammatory microenvironment in BTC precursor lesions. Methods Immunohistochemistry was employed to assess tumour-infiltrating immune cells in tissue samples from patients, for whom precursor lesions were identified alongsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…A growing body of evidence suggests that TME, including cancer cells and immune cells, supports tumor growth and evasion [24,25] . Several studies have identified the critical task performed by the ectonucleotidase CD39 in generating this immunosuppressive environment [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that TME, including cancer cells and immune cells, supports tumor growth and evasion [24,25] . Several studies have identified the critical task performed by the ectonucleotidase CD39 in generating this immunosuppressive environment [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that TME, including cancer cells and immune cells, supports tumor growth and evasion (19,20) . Several studies have pointed to the critical task carried out by CD39 in generating this immunosuppressive environment (21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, they are the most commonly encountered immune infiltrating cells within the tumor microenvironment. Of particular concern in CCA is the presence of high levels of M2 macrophages, which have been shown to be strongly associated with carcinogenesis and poor outcomes in with CCA, as evidenced by prior studies (42)(43)(44). TAMs, a subtype of M2 macrophages, exert potent pro-tumor effects.…”
Section: Innate Immune Cellsmentioning
confidence: 99%